Penerapan Tutor Sebaya untuk Meningkatan Keaktifan dan Kompetensi Siswa dalam Menggambar AutoCAD - Putranto Putranto (Universitas Muhammadiyah Magelang, 2020)
This study aims to improve students’ competence in drawing AutoCAD through peer tutors. It involved students of Class XI Machine A. It was a Class Action Research carried out at SMK Negeri 1 Magelang in the Mechanical Engineering Program in the Academic Year 2017/2018. The results showed that peer tutors increased students’ learning activeness. There was also an increase in learning outcomes in cycle I and cycle II and there was an increase in activeness in each cycle. The mean scores in the pre-cycle was 71.61, increasing in cycle I with 75.84 and again in cycle II with 85.61. Thus both hypotheses were accepted.